Incidental Finding of Bicornuate Uterus during Caesarean Section: A Case Report - Raymond Surya; Edward Sugito Manurung; Ekarini Aryasatiani; Andrew Pratama Kurniawan; Ramot Arif Banamtuan; Charles Yulian Boru; Leomard Evan Mella; Budi Iman Santoso (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: The prevalence of uterine anomalies is estimated from 3% to 5% in the general population. This report would like to discuss a case of successful pregnancy outcome at term delivery in patient with bicornuate uterus in district area of Indonesia Soe, East Nusa Tenggara, Indonesia.Case Report: A 30-year-old first gravida with 39 weeks of gestation coming for elective cesarean section due to primipara in breech pregnancy. There was baby girl born in 2,500 grams of birthweight. During exploration of uterus, both tubes and ovaries, there was found bicornuate uterus with a single common cervix. We found both kidneys in normal size, bicornuate uterus with thickening of endometrial line in left side and normal endometrial line in right side. We measured that the septum was 38 mm. Both mother and baby were healthy at discharge.Result: Bicornuate uterus is usually asymptomatic and diagnosed due to obstetrical complication or accidentally. Uterine abnormalities are increased risk of first and second-trimester loss of pregnancy, preterm delivery <28 weeks, low birth weight babies, and malpresentation at delivery. Imaging plays an essential role in diagnosis and management of bicornuate uterus. It is fundamental to educate a woman with this anomaly. Malpresentation with breech presentation is caused by uterine abnormality of bicornuate uterus.